Entangled in fear : everyday terror in Poland, 1944-1947 - Zaremba, Marcin (Indiana University Press, 2022)
"This is a story about postwar Polish society and its emotions. This is a story of heroes: soldiers, deserters, orphans, and beggars. Now available in English for the first time, Entangled in Fear reveals the broken society where bandits, hunger, bombs, Russia, and countless other threats had an immense influence on Poles as they struggled through the wreckage caused by World War II. Journalist and historian Marcin Zaremba uses sociology, psychology, and history to explore collective fear in official documents and the personal papers of those who were left to survive in postwar Poland. In doing so, he reveals how fear of famine and epidemics, sexual violence and looting, joblessness and invasion led directly to collective action on the part of Poles. A groundbreaking work, Entangled in Fear challenges the reader to consider how emotions have shaped human history and how a more serious engagement with emotions is key to a fuller understanding of the past"--